The Workplace Fun as Moderator Variable between Leadership Virtuousness and Organizational Brilliance (Applied study at the University of Kufa) - جياد علي رزاق (Journal of Economics and Administrative Sciences, 2017)
Abstract The current research tested the interactive role between the workplace fun and the leadership virtuousness in the organizational brilliance, in a sample of the teaching staff at the University of Kufa reached (325 staff) out of (2069) professor. The research based on hypothesis model which reflect the research hypotheses from main variables presented the leadership virtuousness (optimism, forgiveness, trust, compassion and integrity) for moderating affect with the workplace fun (fun activities, Coworker socializing, manager support for fun). The organizational brilliance will increase in case of providing sub-variables which (leadership brilliance, service & innovation brilliance, and knowledge brilliance). The questionnaire was used as the major method for the data collection, hired a number of statistical methods for validating the research hypotheses such as computational variable and the standard deviation and simple correlation coefficient, structural equation modeling and multiple regression analysis. It was identical to the search results most hypotheses which formulated a set of recommendations to hasten the most important the provision and to create fun environment for employees as well as using leadership virtuousness practices and adaptation in line with the requirements of the current stage and the cumulative pressures of prior periods which will reflect the organizational brilliance of the organization.